Aportes positivos de la informalidad laboral a la economía (2014)
This paper seeks to identify positive contributions to the economies associated with informal production activities, analyzing in particular the Colombian case. It was found that after the great crisis of the late nineties in Colombia, the correlation between formality and informality went from negative to positive. From that period the analysis of the relationship between formal and informal production deepens, inferring a symbiotic growth of the two sectors. Furthermore it is concluded that informal employment contributes positive effects for the stability and growth of the Colombian economy.